PERTUMBUHAN KEDELAI (Glycine max [L.] Merrill) VARIETAS ANJASMORO DENGAN PEMBERIAN BIOURIN KAMBING (Capra aegagrus hircus) - Hamid, Abd.; Linda, Riza; Mukarlina, Mukarlina (Universitas Tanjungpura, 2020)
Soybean (Glycine max [L.] Merrill) Anjasmoro variety is one of the superior soybean varieties widely cultivated in West Kalimantan. The growth of soybean can be increased by applying liquid organic fertilizer namely goat biourine. The purpose of this study was to determine the goat biourine quality and the effect of the application of goat biourine on the growth of Anjasmoro variety soybean plants. This study uses a Completely Randomized Design (CRD) consisting of five treatments, namely without biourine/control, 100 mL/L biourine, 200 mL/L biourine, 300 biourine mL/L and Â 400 mL/L biourine. Each treatment was repeated 5 times to obtain 25 experimental units. The analysis of goat biourine showed the value of C-Organic 2.03%, pH 4.83, N 0.72%, P 0.004% and K 0.234%. The results showed that apply of goat biourine had a significant effect on plant height, number of leaves, shoot wet of weight, shoot dry of weight, number of branches, number of root nodules and the number of effective root nodules, but it had not a significant effect on root wet of weight and root dry of weight.